The Influence of Video-Based Media on the Knowledge of Family Planning Acceptor Mothers About the Importance of Family Planning in the Lawawoi Health Center Work Area - Putri, Maidina; Handayani, Sri; Dewi, Ratna; Hamzah, Ricda Nurhikmayanti; Fahamsya, Arifina; Iskandar, Etika; Yermi, Yermi (International Journal of Health Sciences, 2024)
Low knowledge and wrong perceptions about family planning and contraceptives cause women to be afraid of using contraceptives. This is an indicator of high maternal mortality rates, especially in countries with high population growth rates but with low contraceptive prevalence. Providing video-based media as an audiovisual medium can help as a way to convey effective information to increase public knowledge. The aim of this research is to determine the influence of video-based media on the knowledge of family planning acceptors about the importance of family planning in the Puskesmas work area. This research uses a quantitative type of research with an experimental design research method, namely pre-experimental with a one-group pretest-posttest design approach. Sampling used a non-probability sampling technique, namely purposive sampling. Data was collected using a questionnaire and analyzed by conducting a non-parametric statistical test, namely the Wilcoxon Signed-Rank Test. The research results showed that it was accepted, which means that there was an influence of video-based media on the knowledge of family planning acceptors about the importance of family planning. The conclusion in this research is that there is an influence after providing video-based media on the knowledge of family planning acceptor mothers about the importance of family planning in the work area of the Community Health Center.